PSIX-15 Intake of corn stover plant parts by feedlot beef steers. (30th November 2020) - Karls, Caleb; Shinners, Kevin; Schaefer, Dan
Abstract: Corn stover supports feedlot operations in intensive corn producing regions. A single-pass corn grain and stover harvest system was developed to increase efficiency of field operations and capture different anatomical fractions than are typically harvested with conventional corn stover. The objectives were to feed beef steers diets that included a roughage component consisting of harvested corn residue in chopped form from conventional corn stover bales (CST) or single-pass bales (SPB). Whole-plant corn silage (WPCS) served as a control. Steers (n = 90, 5 pens/treatment) were fed during Grow (84 d) and Finish (66 d) phases to assess consumption of corn plant botanical fractions and calculate net energy values of the stover feeds. Cattle consumed a larger proportion of stover as cob (P < 0.001) and less as stalk (P = 0.001) when stover was offered as SPB rather than CST. These differences are consistent with the fractional distribution of botanical components offered. During the Grow phase, cattle fed WPCS had greater (P = 0.018) daily gains (1.27 kg d -1 ) than cattle fed the SPB (1.14 kg d -1 ) and CST (1.08 kg d -1 ), and were more efficient than CST cattle. Steers sorted corn stover during both phases and consumed 52.5% of corn stover offered. SPB cob intake was 70% greater than CST cob intake (P < 0.01) indicating if more cob fraction is available, cattle will consume more. There was no treatment effect on final body weight (P = 0.37) or growth rate (P = 0.12) during the Finish phase. Stover NEm and NEg were calculated using Dairy NRC (2001) methods for SPB (1.04 and 0.49 Mcal kg -1 ) and CST (0.98 and 0.44 Mcal kg -1 ), respectively. In conclusion, there is evidence that CST and SPB can substitute for WPCS in beef feedlot diets without adverse effects on overall steer performance.